The Relationship Between Corporate Social Responsibility and Employees' Pro-Environmental Behavior at the Workplace Among Manufacturing Industries - Kamaruddin, Nor; Azizan, Anim Zalina; Tong, Sheau Yun (Research in Management of Technology and Business, 2021)
Governments and academics are more conscious of environmental concerns and are actively seeking solutions to the many problems caused by contemporary industrial, economic, and human activity. Human behaviours, for example pollution, misuse of natural resources, raw materials, energy, have led to a large number of environmental issues. Thus, research on fostering pro-environmental behaviour (PEB) is necessary to address these problems, since individual PEB behaviours have an effect on organisational environmental sustainability. Hence, some organization have started to utilize social responsibility (CSR) as useful tool for facilitating successful company functioning, social growth and environmental sustainability. However, there are still limited studies to explore the relationship between CSR and PEB in the workplace. Therefore, the purpose of this study is to seeks the relationship between CSR and employees' PEB at the workplace among manufacturing industries in Pahang. Through an online survey, data were gathered from 230 respondents from Pahang's industrial sectors. The research employed convenient sampling techniques. Additionally, the descriptive and correlation analysis conducted to analyze the level of CSR and PEB and the relationship between CSR and employees’ PEB at workplace. The results presented are that the manufacturing sectors in Pahang have a high degree of CSR and PEB at work. Moreover, CSR is found to has a significant relationship with the employees' PEB at the workplace among manufacturing industries in Pahang.